احترافية القائم بالاتصال لدى جريدة الجديد و التحرير وفق نظرية حارس البوابة - الخذير، سعد, فرحات حميده، عبد الحكيم (جامعة الوادي university of Eloued, 2020)
Study summary This study aims to identify the professionalism of those who communicate in the written press through the extent of their commitment to the standards represented in the subjective standards that take into account the scientific qualification, the experience in the journalistic work, the form of their association with the newspaper and the nature of work in it, and the professional standards represented in the extent of their commitment to objectivity, accuracy in content and depth of press coverage And the safety of society's style and standards through the extent of their commitment to everything that offends society, taking into account its components such as customs, traditions, culture, religion, and the public's criteria for deleting and amending false information that would lead to shadowing the audience as well as the volume of some news about the public for the sake of the public interest and thus presenting A sound media material that is characterized by health and credibility, far from subjectivity and falsification of facts
مذكرة ماستر إعلام واتصال تخصص سمعي بصري
Keywords: الاتصال، الصحافة المكتوبة بالجزائر; Contact, la presse écrite en Algérie; Contact, the written press in Algeria